2012
DOI: 10.3389/fmicb.2012.00293
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter-scale patterns of phylogenetic and trait diversity in a salt marsh microbial mat

Abstract: Intertidal microbial mats are comprised of distinctly colored millimeter-thick layers whose communities organize in response to environmental gradients such as light availability, oxygen/sulfur concentrations, and redox potential. Here, slight changes in depth correspond to sharp niche boundaries. We explore the patterns of biodiversity along this depth gradient as it relates to functional groups of bacteria, as well as trait-encoding genes. We used molecular techniques to determine how the mat’s layers differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 109 publications
(143 reference statements)
4
51
0
Order By: Relevance
“…Following previous notions of scale dependency in plant communities (Levin, 1992;Cavender-Bares et al, 2006Swenson et al, 2006Swenson et al, , 2007 and the idea of beta-versus alpha-niche (Silvertown et al, 2006a, b), we might postulate that large-scale processes such as climatic tolerances (beta-niche) may be better evidenced by broadly resolved community profiles ( Figures 1a and b); whereas, small-scale processes such as biotic interactions and microhabitat differentiation (alpha-niche) may only be evident with fine-level classification data (Figure 1c). With respect to prokaryotes with small cell size and short generation time (as considered in this study), a typical sampling setup probably emphasizes the effect of β-niche (evidenced by broadly resolved taxonomic data), whereas the effect of α-niche may be underestimated because of measurement limitations for biotic properties and microhabitat conditions (Ranjard and Richaume, 2001;Armitage et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Following previous notions of scale dependency in plant communities (Levin, 1992;Cavender-Bares et al, 2006Swenson et al, 2006Swenson et al, , 2007 and the idea of beta-versus alpha-niche (Silvertown et al, 2006a, b), we might postulate that large-scale processes such as climatic tolerances (beta-niche) may be better evidenced by broadly resolved community profiles ( Figures 1a and b); whereas, small-scale processes such as biotic interactions and microhabitat differentiation (alpha-niche) may only be evident with fine-level classification data (Figure 1c). With respect to prokaryotes with small cell size and short generation time (as considered in this study), a typical sampling setup probably emphasizes the effect of β-niche (evidenced by broadly resolved taxonomic data), whereas the effect of α-niche may be underestimated because of measurement limitations for biotic properties and microhabitat conditions (Ranjard and Richaume, 2001;Armitage et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the taxa.labels algorithm with presence/absence option, mean MPDSES values of the activated sludge increased significantly as the disturbance progressed: 0.89 ± 0.62 (pre-disturbance) to a maximum of 3.23 ± 0.48 during the 3-day SRT and recovery period followed by a return to pre-disturbance levels, 1.50 ± 0.80. The inability of the independent swap algorithm to detect niche-based community assembly is likely a result of its known conservatism (Kembel, 2009;Armitage et al, 2012), but does not change our interpretation of phylogenetic structure. limiting similarity) (MPDSES = 2.95 ± 0.57, P < 0.005) and indicate that co-occurring species are significantly less related than expected by chance.…”
Section: Disturbance Drives Phylogenetic Community Structurementioning
confidence: 99%
“…The millimetre scale vertically stratified communities and steep physicochemical gradients give ample opportunities for niche differentiation and the co‐existence of competing microorganisms, but few studies actually considered aspects of phylogenetic clustering and trait diversity along these physicochemical gradients. Armitage and colleagues () observed remarkable differences in microbial diversity when analysing different layers of a salt marsh microbial mat. They concluded that habitat filtering was an important factor for the assembly of these mat layers, except for the top layer of cyanobacteria where the phylogenetic diversity was high and trait richness relatively low.…”
Section: Diversity Of Microbial Mats and Diatom Biofilmsmentioning
confidence: 99%